PROBLEM HUKUM PENARIKAN HIBAH OLEH ORANG TUA TERHADAP ANAKNYA PERSPEKTIF HUKUM PERDATA DAN HUKUM ISLAM - Abd. Rahman Saleh; Imam Fawaid (Fakultas Syariah dan Ekonomi Islam, Universitas Ibrahimy, 2021)
Humans as social beings need each other and must complement each other. However, the relationship between humans will be well established if it is supported by the rules that govern the relationship. The relationship between parents and their children has meaning if between the two there are rights and obligations to each other. In the sense that parents have rights and obligations to their children, as well as a child to his parents. One of the actions that make a child and his parents better is the provision of grants. A grant is a legal act that results in the transfer of rights from one person to another. In general, grants can be understood as giving that is done voluntarily by transferring the rights to an object to another person. Both movable and immovable objects. But not infrequently grants given by people who know their children are withdrawn because there are several problems that occur. In this article, we will discuss the legal problem of withdrawing grants by parents to their children.